PROBLEM ISSUES OF ACCOUNTING AND VALUATION OF ENVIRONMENTAL DAMAGE - T. Rogulenko (Вестник университета)
The article discusses the role of accounting information, the basic organizational and functional issues accounting and valuation of environmental damage with the implementation of the principle of payment for the exploitation of the natural wealth of the country and implementation of the principles of ecologically certified environmental management. Analyzes the provisions of the draft Environmental code, the adoption of which will be the panacea for all problems in the field of ecology. Author concludes that the existing system of information support of environmental management projects neither the quality nor the amount and detail of the indicators does not meet the requirements of specialists of state bodies of management and corporate management. Suggestions are given on how relatively accurate identification of costs, expenses, income, assets, liabilities in the total array of economic life facts recorded in the accounting system, the development of the practice of formation of accounting policies used and the optimization methods of analytical accounts for the accounting and valuation of environmental damage in accordance with the needs of the business management system.